2011
DOI: 10.3389/fnagi.2011.00017
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Measurement of the Components of Attention of Older Adults using the Two Versions of the Attention Network Test: Stability, Isolability, Robustness, and Reliability

Abstract: Ishigami and Klein (2010) showed that scores of the three attention networks (alerting, orienting, and executive control) measured with the two versions of the Attention Network Test (ANT; Fan et al., 2002; Callejas et al., 2005) were robust over 10 sessions of repeated testing even though practice effects were consistently observed especially in the executive network when young adults were tested. The current study replicated their method to examine robustness, stability, reliability, and isolability of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 52 publications
4
14
1
Order By: Relevance
“…This finding confirmed the dependence between attention networks [8], [11], [24], [25], [28], [32], [33], [53]. Similar to Callejas et al's [24], [25] studies using double-modality paradigm and Fan et al [26]'s study using single-modality paradigm, our results showed an inhibition from alerting network to executive function network.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding confirmed the dependence between attention networks [8], [11], [24], [25], [28], [32], [33], [53]. Similar to Callejas et al's [24], [25] studies using double-modality paradigm and Fan et al [26]'s study using single-modality paradigm, our results showed an inhibition from alerting network to executive function network.…”
Section: Discussionsupporting
confidence: 91%
“…The ANT combines Posner's cued reaction time (RT) task [5] and Eriksens' flanker task [6] to differentiate independent attention components in one paradigm. This paradigm consistently induced remarkable main effects of attention networks and has been demonstrated to be reliable between sessions [1], [7], [8]. In the past decade, it has been widely employed in brain functional [9][12], developmental [8], [13], [14], genetic [15][17], and psychiatric investigations [18][23] to test normal and abnormal attention abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that the learning effect of repetitive testing on ANT neuropsychological testing confounds the association linking sleep deprivation with ANT parameters corroborates others' findings 32. Ishigami and Klein examined the reliability and robustness of ANT over 10 sessions of repeated testing, and found that despite the learning effect, the ANT remained a reliable test of the brain's attentional networks.…”
Section: Discussionsupporting
confidence: 89%
“…Similar practice effects were observed for the first few days of testing on the ANT conflict effect by Ishigami and Klein (17,18), and as a consequence, they noted the need for a control group in some designs. Given the significant between-group differences and the lack of an interaction between the concussed and the control groups across the testing sessions, these tasks appear to remain sensitive to the disruptions in executive function induced by concussion for up to 2 months postinjury.…”
Section: Discussionsupporting
confidence: 69%